Pengaruh Kedisiplinan Terhadap Hasil Belajar Siswa di SMP Don Bosco Tomohon - Untu, Hadi Ignatius; Landayo, Wilson Y.; Pangemanan , Henny; Sugiarto , Novena (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
This research aims to examine the influence of learning discipline on Catholic Religious Education learning outcomes for class VII students at Don Bosco Tomohon Middle School. The method used was quantitative with 60 class VII students participating. The instruments used consist of questionnaires to measure learning discipline and test results as well as evaluations of the applicable curriculum to measure Catholic Religious Education learning outcomes. The results of instrument testing show that the instrument used can be considered valid and reliable. The data were analyzed using simple regression analysis and the results showed that there was a significant influence between learning discipline and students' Catholic Religious Education learning outcomes with a determinant coefficient of 0.590. From these results it can be concluded that learning discipline contributes 59% to student learning outcomes, while 41% is influenced by other factors. The implication of this research is the important role of learning discipline in improving student academic achievement, as well as providing input for teachers and schools in developing more effective learning strategies.